1996
DOI: 10.1017/s0007485300039201
|View full text |Cite
|
Sign up to set email alerts
|

Weather associated with spring and summer migrations of rice pests and other insects in south-eastern and Eastern Asia

Abstract: Trajectory analysis of the windfields at 10 m and 1.5 km was used to determine the direction and extent of windborne movements of insects trapped in spring and summer in south-eastern and eastern Asia for the period 1968 to 1985. Approximately 2500 trajectories, depicting the movements of airborne particles, were constructed where temperatures were high enough (>=10°C) to allow flight and where wind speeds (> =5 kmh−1) were expected to lead to downwind displacements. Trap catches were dominated (97%) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The long-term migration analysis suggested that early migrations from the Philippines to southern China were likely to have occurred. Early migrations observed on ships off the coast of Guangdong province from March to June 1984 were analyzed by two-dimensional trajectory analysis, and their source was found to be the Philippines (Mills et al 1996). In addition, it is known that planthoppers emerge year-round in the Philippines because of its tropical climate.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term migration analysis suggested that early migrations from the Philippines to southern China were likely to have occurred. Early migrations observed on ships off the coast of Guangdong province from March to June 1984 were analyzed by two-dimensional trajectory analysis, and their source was found to be the Philippines (Mills et al 1996). In addition, it is known that planthoppers emerge year-round in the Philippines because of its tropical climate.…”
Section: Discussionmentioning
confidence: 99%
“…After a series of northward expansions from the source through a few generations, N. lugens invade East Asia (Cheng et al 1979;Sogawa and Watanabe 1992;Zhou et al 1995). Weather associated with these spring and summer migrations of N. lugens are often analysed by many workers (Watanabe and Seino 1991;Kisimoto and Sogawa 1995;Mills et al 1996;Turner et al 1999;Otuka et al 2005b). A hypothesis of autumn return migration from temperate China to hibernating areas was also proposed by Cheng et al (1979).…”
Section: Introductionmentioning
confidence: 99%
“…1995). Weather associated with these spring and summer migrations of N. lugens are often analysed by many workers (Watanabe and Seino 1991; Kisimoto and Sogawa 1995; Mills et al. 1996; Turner et al.…”
Section: Introductionmentioning
confidence: 99%
“…After a series of northward expansions over a few generations, N. lugens invades as far as temperate East Asia (Cheng et al, 1979;Sogawa & Watanabe, 1992;Zhou et al, 1995). There have been many reports on the association between weather and spring and summer migrations of N. lugens (Watanabe et al, 1991;Kisimoto & Sogawa, 1995;Mills et al, 1996;Turner et al, 1999;Otuka et al, 2005Otuka et al, , 2006. Cheng et al (1979) proposed an autumn return migration from temperate China to hibernating areas, which has been supported by the detection of the southwestward mass movement of the planthopper by radar observations (Riley et al, 1991(Riley et al, , 1994 and weather analysis (Rutter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%